Introduction à l’étude de l’assurance-cautionnement - P., G. (Assurances, 1982)
In the eyes of the author, despite the meagre number who would agree with him thereupon, surety bonds constitute a form of insurance. In his exposé, he examines and analyses the nature and various aspects of surety bonds and surety bond business in Canada, the United States and France. In the second section of his text, G.P. acquaints the reader with the key provisions of actual surety bond contracts in Canada and France.